Therapy - Fitzek, Sebastian (Head of Zeus, 2023)
Intro – Also by Sebastian Fitzek – Title Page – Copyright – Dedication – Contents – Prologue – Chapter 1 – Years later – Chapter 2 – Five days before the truth, Parkum – Chapter 3 – Chapter 4 – Chapter 5 – Chapter 6 – Chapter 7 – Four days before the truth, Parkum – Chapter 8 – Chapter 9 – Chapter 10 – Chapter 11 – Three days before the truth, Parkum – Chapter 12 – Chapter 13 – Chapter 14 – Chapter 15 – Chapter 16 – Room 1245, Berlin-Wedding Psychosomatic Clinic – Chapter 17 – Two days before the truth, Parkum – Chapter 18 – Chapter 19 – Chapter 20 – Chapter 21 – Chapter 22 – Room 1245, Berlin-Wedding Psychosomatic Clinic – Chapter 23 – Chapter 24 – Chapter 25 – Chapter 26 – The day before the truth, Parkum – Chapter 27 – Chapter 28 – Chapter 29 – Chapter 30 – Chapter 31 – Chapter 32 – Chapter 33 – Chapter 34 – Room 1245, Berlin-Wedding Psychosomatic Clinic – Chapter 35 – Chapter 36 – Chapter 37 – Day of Reckoning, Parkum – Chapter 38 – Chapter 39 – Chapter 40 – Chapter 41 – Chapter 42 – Chapter 43 – Chapter 44 – Chapter 45 – Chapter 46 – Chapter 47 – Chapter 48 – Chapter 49 – Chapter 50 – Chapter 51 – Chapter 52 – Chapter 53 – Chapter 54 – Chapter 55 – Chapter 56 – Chapter 57 – Nine days later, Berlin-Wedding Psychosomatic Clinic – Chapter 58 – Chapter 59 – Chapter 60 – Epilogue – Six months later, Côte d'Azur – Acknowledgements – About the Author – An Invitation from the Publisher.
Description based on publisher supplied metadata and other sources
Keywords: Surgery